Nutritional profile comparison of wild and Tagal indigenous mahseer (Tor duoronensis) from Borneo - Rossita Shapawi,; Najamuddin Abdul Basri,; Yong, Annita Seok-Kian; Lim, Leong Seng; Ching, Fui Fui (Penerbit Universiti Kebangsaan Malaysia, 2025)
Little is known about the nutritional status of mahseer (Tor duoronensis), a high-value indigenous freshwater species of Borneo. The present study evaluated the proximate, fatty acid, and amino acid compositions in carcasses of juvenile wild and conserved (tagal system) mahseer. The crude lipid content of the wild-caught fish was significantly higher (P < 0.05) than tagal fish. Mahseer from tagal system contained significantly higher (P < 0.05) fatty acid concentrations of C14:0, C15:0, C16:0, C16.1, C17:0, C18:0, C18:1 n9t, C20:0, C20:4n6, C20:5n3, and C22:6n3, and lower concentrations of C12:0, C18:1 n9c, C18:2 n6c, C18:3 n3, C20:1, and C21:0 fatty acids than wild mahseer. The percentages of total saturated fatty acids and n-3:n-6 ratio were higher in the tagal system than in wild mahseer. Tor duoronensis harvested from the tagal system showed higher total amino acid concentration (756.74 ± 225.21 ng g-1) compared to wild fish (652.10 ± 249.50 ng g-1). Among the amino acid recorded, cysteine content was high in both wild (147.12 ± 206.62 ng g-1) and tagal fish (164.37 ± 229.39 ng g-1). Nine essential amino acids (histidine, arginine, threonine, valine, methionine, lysine, isoleucine, and phenylalanine) that are important in fish’s metabolic and physiological responses were present in both fish groups. This study indicates that the biochemical composition of Tor duoronensis was significantly influenced by their habitat, and these differences may be explained by the components of the fish’s diet. The information generated from this study is beneficial for developing nutritionally balanced practical feed for this species.